Fundamentals of Cosmology - Rich, James (Springer Berlin Heidelberg : Imprint: Springer, 2010)
The book is aimed at astrophysics students and professional physicists who wish to understand the basics of cosmology and general relativity as well as the observational foundations of the LambdaCDM model of the Universe. The book provides a self-contained introduction to general relativity that is based on the homogeneity and isotropy of the local universe. The simplicity of this space allows general relativity to be presented in a very elementary manner while laying the foundation for the treatment of more complicated problems. The new edition presents the most recent observations, including those of CMB anisotropies by WMAP and of Baryon Acoustic Oscillations by SDSS. Future observational and theoretical challenges for the understanding of dark energy and dark matter are discussed. From 1st edition reviews: "The book provides a comprehensive and thorough explication of current cosmology at a level appropriate for a beginning graduate student or an advanced and motivated undergraduate. ... This is an extremely valuable contribution in the field, which has been changing rapidly ... provides a good look at the intellectual effort and a solid foundation for the new discoveries soon to come." (Physics Today, September 2002) "All these exciting developments are laid out in a very accessible form in this textbook especially written for senior undergraduates or graduates from various backgrounds. It deals in a very nice and explicit form with the basic ideas of cosmology and general relativity (...). This is a fine textbook and would be very enjoyable for private study. (The Physicist, 2001).